The Influence of Digital Service Innovation, Human Resource Quality, and the Effectiveness of Health Promotion on Community Satisfaction and Participation at Babatan Community Health Center - Muhammad Rifky; Bernard T. Widjaja (Green Publisher Indonesia, 2026)
This study aims to analyze the influence of digital service innovation, the quality of human resources, and the effectiveness of health promotion on community satisfaction and participation in health programs at the Batanan Health Center. This study uses a quantitative approach with a survey method on people who are users of Batanan Health Center services. Data were collected through a Likert scale questionnaire and analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) to test the relationships between variables. The results of the study are expected to provide an empirical picture of the extent to which digital service innovation, health worker competence, and the effectiveness of health promotion are able to increase satisfaction and encourage community participation in health programs. The findings of this study are expected to be a consideration for Puskesmas managers and the government in improving the quality of technology-based health services, strengthening human resources, and optimizing health promotion to achieve more effective and sustainable public health services.